Analysis of Students' Ability to Solve Higher Order Thinking Skill Questions on Reaction Rate Materials in 11th Grade of MAN 1 Pontianak - Lestari, Indah; Enawati, Eny; Ulfah, Maria; Hairida, Hairida; Erlina, Erlina (Universitas Pendidikan Mandalika, 2024)
High Order Thinking Skill is one of the most important skills in the 21st century. This study aims to describe the ability of students to solve Highter Order Thinking Skill (HOTS) questions in the reaction rate material in class XII MAN 1 Pontianak. The HOTS indicator in this study is the ability to analyze (C4). The method used in this study is descriptive. The subject of the study is 11th Grade students of MAN 1 Pontianak for the 2023/2024 school year consisting of 37 students. The instruments used are HOTS question sheets on validated reaction rate materials and interview guidelines. The results of this study show that there are 2.7% of students with high ability and meet the criteria for analysis, 13.5% of students with medium ability and are able to analyze problems but there are still mistakes, and 83.7% of students with low ability are 83.7%.